Fragmentation As Gender Trap: A Feminist Reading Of Selected Dramas By Henrik Ibsen And George Bernard Shaw - Ali, Azhar Jasim (2015)
Henrik Ibsen dan George Bernard Shaw sering dianggap sebagai individu yang memperjuangkan hak wanita